Noise Pollution in Schools of Hanoi City: Status and Sollutions - Anh, Nguyen Ngoc; Huong, Bui Thi Thanh; Trang, Hoang Gia (VNU Journal of Science: Education Research, 2022)
Noise pollution in the school environment is creating significant effects on the mental health of teachers and students, indirectly reducing the quality of education. By integrating IoT technique and GIS, the results of the project on investigating the situation of noise pollution at 362 schools in Hanoi (Primary, Secondary, High schools) for 2 years (2019-2021) showed four noise pollutions regions: high pollution, medium pollution, low pollution, and no pollution. At the same time, the study pointed out that the school sites have a high risk of noise pollution. The data collected before COVID 19 and in COVID 19 showed that noise pollution reduced 20 - 30dB. From the status of the noise pollution at schools in Hanoi, the research group has recommended some measurements to reduce noise pollution in schools in Hanoi city.